The Nature of Ion‐Pair Recognition by Tetra‐phosphonate Calix[4]pyrroles. Issue 3 (12th February 2018) - Wang, Teng; Liu, Jingjing
Abstract: The tetra‐phosphonate calix[4]pyrroles can function as multitopic receptors for ion‐pair recognition, and this process is mainly driven by noncovalent interactions (NCIs). In the present contribution, the NCIs in ion‐pair recognition by two representative receptors iiii and oooo, which differ in the relative orientation of the phosphonate groups, were explored by density functional theory calculations. The decomposition of the interaction energy suggests that electrostatic plays a dominant role in ion‐pair recognition, and it dictates that contact and separated arrangements are the favorable binding modes for iiii and oooo receptors, respectively. Furthermore, the calculation results predict that iiii receptors show superior binding affinities for organic chloride salts compared to oooo receptors. This study reveals the nature of ion‐pair recognition by tetra‐phosphonate calix[4]pyrroles, while providing valuable insights into the design of novel calix[4]pyrrole‐based ion‐pair receptors. Abstract : To characterize the contributions of noncovalent interactions to ion‐pair recognition by tetra‐phosphonate calix[4]pyrroles, the state‐of‐the‐art computational methods, namely symmetry‐adapted perturbation theory (SAPT) calculations, were carried out on this large and complex system.